Shaharom Husain - Abdul Rahman Hanafiah (Dewan Bahasa dan Pustaka, 2006)
Biography, literary criticism, and works of Shaharom Husain, a Malaysian writer, teacher, and playwright from Johor
Includes bibliographical references (p. 257-259) and index
Keywords: Biografie